Synthesis and biological evaluation of thiazole and thiadiazole derivatives as potential anticancer agents - ŞENKARDEŞ, SEVİL (My University, 2022)
A new series of 4-methyl-2-{2-[(aryl)methylidene]hydrazinyl}-1,3-thiazole (2a-i), N-(4-acetyl-5-aryl)4,5-dihydro-1,3,4-thiadiazol-2-yl)acetamides (3a-b) and N-(5-(4-(substituted phenyl)-1,3,4-thiadiazol-2-yl)acetamides (3c-i) were synthesized by the reaction of 2-((aryl)methylene)hydrazine-1-carbothioamides (1a-i) and acetic anhydride or chloroacetone. The cytotoxic activities of the products were evaluated by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay against Hela cervical cancer, MCF-7 breast carcinoma and HT-29 colorectal cancer cell lines. Thiazole based compounds 2a, 2b, 2f and 2i, bearing 4-bromothiophen-2-yl, naphthalen-2-yl, 2,5-difluorophenyl and 4-(trifluoromethoxy)phenyl moieties, respectively; also N-(4-acetyl-5-(naphthalen-2-yl)-4,5-dihydro-1,3,4-thiadiazol-2-yl)acetamide (3b) and N-(5-(2,6-difluorophenyl)-1,3,4-thiadiazol-2-yl)acetamide (3d) exhibited significant anticancer activity against three cancer cell lines. Moreover, these active compounds were further evaluated by apoptotic protein levels. The results showed that these thiazole and thiadiazole compounds induced apoptosis of cancer cells.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; İnorganik Kimya; Temel Bilimler; Chemistry; Biochemistry; Bioinorganic Chemistry; Inorganic Chemistry; Natural Sciences; KİMYA, İNORGANİK VE NÜKLEER; Temel Bilimler (SCI); KİMYA, ORGANİK; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, ORGANIC; Organik Kimya; İnorganik kimya; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Organic Chemistry; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Anticancer activity; thiadiazole; thiazole; apoptosis; thiosemicarbazone; STRUCTURAL-CHARACTERIZATION; HYBRIDS; 1,3,4-THIADIAZOLE; INHIBITION; CANCER; BAX